Understanding human error in mine safety [ - Simpson, Geoff; Horberry, Tim; Joy, Jim (Ashgate, 2009)
The consideration of human factors issues is vital to the mining industry. This book intends to provide the reader with a much-needed overview of human factors within the mining industry, in